Crystal Structure, Raman Spectroscopy and Dielectric Properties of New Semiorganic Crystals Based on 2-Methylbenzimidazole - E. V. Balashova; F. B. Svinarev; A. A. Zolotarev; A. A. Levin; P. N. Brunkov; V. Yu. Davydov; A. N. Smirnov; A. V. Redkov; G. A. Pankova; B. B. Krichevtsov (Crystals, 2019)
New single crystals, based on 2-methylbenzimidazole (MBI), of MBI-phosphite (C16H24N4O7P2), MBI-phosphate-1 (C16H24N4O9P2), and MBI-phosphate-2 (C8H16N2O9P2) were obtained by slow evaporation method from a mixture of alcohol solution of MBI crystals and water solution of phosphorous or phosphoric acids. Crystal structures and chemical compositions were determined by single crystal X-ray diffraction (XRD) analysis and confirmed by XRD of powders and elemental analysis. Raman spectroscopy of new crystals evidences the presence in crystals of MBI-, H3PO3-, or H3PO4- and water molecules. Dielectric properties of crystals reveal strong increase and low frequency dispersion of dielectric constant and losses at heating, indicating the appearance of proton conductivity. At low temperatures in MBI-phosphate-2, an increase of dielectric constant analogous to quantum paraelectric state is observed.